(untitled) (Linguostylistic Studies, 2020)
The Ukrainian-Polish border-line region opens up a lot of research prospects, especially when it comes to the territories of the so-called Zakerzonie region, namely Kholmshchyna, Nadsiannia and Lemkivshchyna. They are of particular interest in terms of their location and combination of several cultures since they were the westernmost regions of the Ukrainians living within ethnographic areas. As a result of the tragic events of the first half of the twentieth century, related to the relocation of the interstate border and the resettlement of the indigenous ethnic groups from the places of their autochthonous residence the Polish and Ukrainian populations now live both on the territory of their own country and in the neighboring country, where they are one of the national minorities. A well-known Polish folklorist and ethnomusicologist Oscar Kolberg (1814-1890) managed to record and partially publish in the second half of the 19th century the folklore materials of the Khelm region, lost due to the later forced resettlement of the autochthons. Indicative features of the methodology of this tireless collector of folk art were the philological accuracy and completeness of the recorded from the mouth of the respondent material with the phonetic transcription to convey all the nuances of speech. Many border areas have undergone significant changes in their ethnic composition since O. Kolberg’s recordings, so the folklore and ethnographic materials recorded by an authoritative Polish researcher are almost the only source of reconstructing the life, customs, and firstly, an authentic speech of the population of these regions. The article analyzes the dialect lexical units attested in the records of the Khelm folklore of the second half of the XIX century, revealed by Oscar Kolberg. The author focuses on the description of names according to the lexical-semantic principle. The information potential of the materials allows segmenting the lexical units into 12 thematically diverse semantic groups which quite fully represent the vocabulary of the conceptual field of a Human and his/her Features, Daily Economic Activity, Life, Nature, Material and Spiritual Cultures, etc. The functioning of the dialect units is not limited to the outlined spheres and to the lexical-semantic groups within them, but they are the most representative.